New marker of B lymphocytes, MB2: comparison with other lymphocyte subset markers active in conventionally processed tissue sections. Issue 2 (February 1987) - Hall, P A; D'Ardenne, A J; Butler, M G; Habeshaw, J R; Stansfeld, A G
Abstract : The use of the murine monoclonal antibody MB2 for identifying B lymphocytes in routinely processed tissue was evaluated and contrasted with the use of the monoclonal antibody UCHL1 for identifying T cells. One hundred and sixty eight surgical biopsy specimens were immunostained with these antibodies, including a wide range of normal and neoplastic non-lymphoid tissues, as well as normal lymphoreticular tissues and lymphomas. Sixty four non-Hodgkin's lymphomas were also examined, of which 51 had been previously phenotypically defined. In selected cases the results were compared with those obtained using two other monoclonal antibodies MB1 and MT1, used for identifying B and T cells, respectively, in paraffin sections. MB1 stained a smaller proportion of B cell tumours than MB2 and staining was, in general, weaker, except in one case of centroblastic lymphoma. MT1 immunoreactivity was comparable with that of UCHL1, except in one case of T lymphoblastic lymphoma (MT1 positive, UCHL1 negative). None of the antibodies is ideal, but, if used as a panel, they permit the separation of B cells and T cells in paraffin sections.